2013
DOI: 10.1002/jsc.1921
|View full text |Cite
|
Sign up to set email alerts
|

Rise and Fall of Microfinance in India: The Andhra Pradesh Crisis in Perspective

Abstract: The crisis of microfinance which erupted in 2010 in Andhra Pradesh has complex causes rooted in Indian history. Indian microfinance institutions pursued reckless growth at all costs and ignored all warnings in a particular environment inherited from the past. Their business model was built on shaky foundations, until a blundering Andhra government stepped in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 14 publications
0
92
0
2
Order By: Relevance
“…Many actors, including international donors, such as the Bill and Melinda Gates Foundation, † and nongovernment organizations, ‡ have pushed to create and expand such groups, viewing them as a grassroots and lowcost mechanism to provide (albeit informal) financial services to the poor. Similarly, the Andhra Pradesh Government in India promoted a self-help group model (Velugu) as an alternative to formal microcredit during a crisis in 2010 (5). The model, which is being explored by many NGOs, is a type of savings group with the added feature of explicit intentions to link groups to formal sector banks for credit after they mature enough [e.g., Plan and CARE (Cooperative for Assistance and Relief Everywhere) have partnered with Barclays for this purpose] (6).…”
mentioning
confidence: 99%
“…Many actors, including international donors, such as the Bill and Melinda Gates Foundation, † and nongovernment organizations, ‡ have pushed to create and expand such groups, viewing them as a grassroots and lowcost mechanism to provide (albeit informal) financial services to the poor. Similarly, the Andhra Pradesh Government in India promoted a self-help group model (Velugu) as an alternative to formal microcredit during a crisis in 2010 (5). The model, which is being explored by many NGOs, is a type of savings group with the added feature of explicit intentions to link groups to formal sector banks for credit after they mature enough [e.g., Plan and CARE (Cooperative for Assistance and Relief Everywhere) have partnered with Barclays for this purpose] (6).…”
mentioning
confidence: 99%
“…Eventually the MFI industry overtook the SHG sector in loan outstanding terms, but not without increasing the average indebtedness of households in Andhra Pradesh (Srinivasan 2010). Interest rates were as high as 31-32% and there was huge competition for clients (Mader 2013). In a survey conducted by Institute of Financial Management Research, it was found that though only 11% of the borrowing was from an MFI, while 84% of the rural households had multiple loans outstanding (Johnson and Meka 2010).…”
Section: Growth Of Microfinance In India Through the Prism Of Andhra mentioning
confidence: 99%
“…Mersland et al (2011) Vlivem špatného řízení rizika a úvěrovému boomu se indický mikrofi nanční sektor dostal do pasti vedoucí k největší mikrofinanční krizi v historii tzv. "Andhra Pradesh Crisis" (Mader a Winkler, 2013). MFIs by měly proto podobně jako komerční banky předcházet podobným scénářům vytvářením dostatečné kapitálové rezervy (Teply a Klinger, 2014), která by zajišťovala v případě tržních otřesů větší stabilitu mikrofi nančního sektoru jako celku.…”
Section: Globalizace Mikrofi Nančního Trhuunclassified